"Heloisa Schneiders da Silva: obra e escritos", organized by Mônica Zielinsky - Fabris, Annateresa (PORTO ARTE: Revista de Artes Visuais, 2013)
The book "Heloisa Schneiders da Silva: obra e escritos" (or "Heloisa Schneiders da Silva: work and writings"), 2010, includes two essays – one from the volume’s organizer Mônica Zielinsky and the other by Gaudêncio Fidelis – a documental section, a chronology, and also reproductions of the artist’s works and pictures from the late 1970s to 2005, year she passed away.